2020
DOI: 10.1007/s00415-020-10065-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk incidence of fractures and injuries: a multicenter video-EEG study of 626 generalized convulsive seizures

Abstract: Objective To evaluate the incidence and risk factors of generalized convulsive seizure (GCS)-related fractures and injuries during video-EEG monitoring. Methods We analyzed all GCSs in patients undergoing video-EEG-monitoring between 2007 and 2019 at epilepsy centers in Frankfurt and Marburg in relation to injuries, falls and accidents associated with GCSs. Data were gathered using video material, EEG material, and a standardized reporting form. Results A total of 626 GCSs from 411 patients (mean age: 33.6 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
(46 reference statements)
1
15
0
2
Order By: Relevance
“…broken bones). [18][19][20] The following results are average values per patient (related to a defined month):…”
Section: Results Of the Initial Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…broken bones). [18][19][20] The following results are average values per patient (related to a defined month):…”
Section: Results Of the Initial Surveymentioning
confidence: 99%
“…Putative concerns about the patient's well-being (e.g., fear of stigmatization or mobility in daily life) are soft factors that should not be a contraindication. [8][9][10][11][12][13][14][15][16][17][18]20 A good half of the wheelchair users even had stronger leg and back muscles after a year in their wheelchairs, without any walking, thanks to supervised physiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, 0.3% of the fractures were directly associated with convulsive seizures and without additional trauma. Frey et al analyzed 411 patients between 2007 and 2019 at epilepsy centers in Frankfurt and Marburg, where 6 patients sustained fractures with no obvious injuries [3] . Salas-Puig et al observed 406 patients with generalized seizures; the rate of accidental fracture associated with generalized seizures was 3.9% [4] .…”
Section: Discussionmentioning
confidence: 99%
“…2 In the recent study, severe adverse events such as fractures, joint luxation, corneal erosion and teeth loosening were observed in 2.1% per generalised convulsive seizure. 3 However, few reports of mandibular fractures as single convulsion, there is a report that refractory epilepsy may be associated with dentoalveolar and mandibular fractures. 4 A systematic review about bone fractures from generalised convulsive seizures reported that the shoulders' fractures were most frequently described (33%) and followed by thoracic and lumber vertebral compression fractures (29%), skull and jaw fractures (8%) and bilateral femoral neck fractures (6%).…”
Section: Descriptionmentioning
confidence: 99%